METODOLOGÍAS ACTIVAS EN EL APRENDIZAJE DE LA LECTO ESCRITURA, DE LOS NIÑOS Y NIÑAS DE SEGUNDO INICIAL PARALELO “C” DE LA UNIDAD EDUCATIVA VIGOTSKY CENTRO, RIOBAMBA, CHIMBORAZO, PERIODO 2018 – 2019 - Espín Pozo, Janella Lizbeth (2019)
This research work entitled “Active methodologies in learning the writing-reading of children initial second parallel "c" of the Educational Unit Vigotsky from Riobamba Chimborazo, period 2018-2019. This research has the objective of determining the active methodologies that help the reading process in the children of the second parallel initial "C" of the Vigotsky Educational Unit, to enhance the process of reading and writing in children contributing dynamically and effectively to further progress in the educational process, it is a social research, the technique used was the observation, it was supported by a practical instrument that is the observation card developing it in class. This is an experimental study as it is working which a sample of 31 children of the aforementioned Educational Unit, which will serve for the analysis and interpretation of results, information will be taken from various sources or bibliographical references, books, for obtain conclusions of an research nature in this way, conclusions of an investigative nature. As a result , it can mention that active methodologies are key to reading and writing teaching by varying traditional and new methods, and setting according to the case.